NRF1 Alleviated Oxidative Stress of Glioblastoma Cells by Regulating NOR1 - Wang, Jiali; Chen, Shuai; Xiang, Wang; Zhu, Qing; Ren, Nianjun (Folia biologica, 2023)
Oxidored-nitro domain-containing protein 1 (NOR1) is a critical tumour suppressor gene, though its regulatory mechanism in oxidative stress of glioblastoma (GBM) remains unclear. Hence, further study is needed to unravel the function of NOR1 in the progression of oxidative stress in GBM. In this study, we evaluated the expression of NOR1 and nuclear respiratory factor 1 (NRF1) in GBM tissue and normal brain tissue (NBT) using quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot (WB), and investigated their relationship. We then induced oxidative stress in U251 cells through H2O2 treatment and conducted Cell Count-ing Kit-8, Transwell and wound healing assays to analyse cell proliferation, invasion and migration. Cell apoptosis was assessed by flow cytometry and TUNEL staining. We also measured the activities of superoxide dismutase and catalase, as well as the level of reactive oxygen species (ROS) using biochemical techniques. Via qRT-PCR and WB, the mRNA and protein expression levels of NOR1 and NRF1 were determined. Chromatin immunoprecipitation (ChIP) assays were applied to validate NRF1's interaction with NOR1. Our results showed that the expression of NOR1 and NRF1 was low in GBM, and their expression levels were positively correlated. H2O2-induced oxidative stress reduced NRF1 and NOR1 expression levels and increased the ROS level. The ChIP assay confirmed the binding of NRF1 to NOR1. Over-expression of NRF1 attenuated the inhibitory effect of oxidative stress on the proliferation, migration and invasion of U251 cells, which was reversed by knockdown of NOR1.
Keywords: Reactive Oxygen Species; proliferace buněk; Nuclear Respiratory Factor 1; oxidative stress; peroxid vodíku; Oxidative Stress; oxidační stres; Humans; transkripční faktor NRF1; reaktivní formy kyslíku; Cell Proliferation; Glioblastoma; Hydrogen Peroxide; NOR1; NRF1; glioblastom; GBM; lidé